Android-based Mobile Rapid Health Assessment in the Disaster Emergency Response Phase - Nur Hidayati; Abdul Rokhman; Karsim; Nilam Fatmawati; Fitria Dewi Sasmita; Rachel Marselino (Babali Nursing Research, 2023)
Introduction : Rapid health assessment (RHA) is an assessment during the disaster emergency response phase that requires a fast, precise, and accurate time so that the damage caused by the disaster and immediate needs of disaster victims can be recognized. Rapid assessment with manual forms will prolong the process of needs assessment and analysis. Android-based RHA applications are made to facilitate rapid assessment so that the type of assistance needed can be determined as soon as possible. The purpose of the study was to create an android-based RHA application, test the validity and usability of the application, and test it on application users. Methods: This research was conducted using a Research and Development design divided into two stages. In stage 1, the application was created, and five experts tested the validity and reliability. Stage 2 was socialization and application trials on 30 disaster volunteers in Lamongan. In this stage, the usability of application was measured by the System Usability Scale. Results: The application components had good validity (I-CVI=1) and reliability (Cronbach’s alpha=0.768). The usability score showed that 84.3% of the users considered the application easy to operate, 83.67% stated that the menu display and features were easy to use, 80% stated that it was comfortable, 81.3% were satisfied with the application features, and 85.7% stated that the application was helpful in disaster. Conclusions: The RHA application is valid, reliable, and usable for general use for rapid health assessment in the disaster emergency response phase.